Intention to migrate among the next generation of Turkish nurses and drivers of migration - ŞAHİN ORAK, NURAY (WILEY, 2021)
Aims To determine the main driving factors affecting the senior nursing students in their decision to migrate and to evaluate the effect of attitude towards migration in career planning. Background In order to promote the nursing workforce, it is important to understand the factors affecting the decisions to migrate. Method A cross-sectional study was conducted with 1,410 Turkish nursing students. The data, which were collected using the Descriptive Form and Attitude Scale for Brain Drain (BD-s), were analysed with the multiple regression and decision tree analysis. Results The mean score of attitudes towards migration was 56.30 +/- 12.09 (min 16- max 80). The main push-pull drivers to migrate were the socio-political factors and working conditions. The BD-s score was higher in the participants, who had overseas experience, had career plans and studied in a metropolitan city. The strongest variable predicting career planning was the attitude towards migration. Conclusion The opinions of the students on career planning and their intentions to migrate indicated that the shortage of nurses would continue in Turkey in the future. Implications for Nursing Management The prospects of the nursing candidates regarding the nursing profession should be addressed considering their expectations for initial salaries, career development and salary increases.
Keywords: driving factors; migration; nursing students; nursing workforce; push and pull factors; EDUCATED NURSES